Editorial: Ecological restoration as a central theme for applied vegetation science - Chiarucci, Alessandro (2007)
Restoration ecology is becoming an important part of applied science, especially because of the pressing need to restore to a pristine state, or to another functionally stable state, many sites that have been degraded by human pressure, pollution, or management. In almost all terrestrial habitats and in many aquatic ones ecological restoration passes through some process of vegetation restoration, since vegetation is vital for ecosystem structure and function. Fittingly, vegetation restoration was a theme of Applied Vegetation Science in 2006. The two issues included 34 papers and a total of 316 pages. The first issue included many papers on the theme Conservation and restoration of the Pinus palustris ecosystem, while the second was fully dedicated to the theme Fens and floodplains of the temperate zone: Present status, threats, conservation and restoration. Restoration of natural vegetation was the aim of most of these papers, using a variety of approaches and methods for the recruitment of structurally important plant species in different ecosystems.